Tratamento cirúrgico de osteomas em face: relato de caso raro - Vieira, Alessandra Fragoso (2019)
Osteomas are benign, slow-growing bone tumors, usually solitary and asymptomatic. Possible controversy, being able to be denominated of greater or smaller, depending on its location. Common in the skull, they are being found in other bones. In the mandible, they affect the condyle and mandibular body, followed by the angle. These tumors can hardly become large and cause facial deformity. The case of the work is to report a case of a 32-year-old patient, normossemic, who helps pay attention to the problem of bone growth in the face. Upon physical examination, the patient presented an extensive swelling of the volume, hard to palpation, in the region of the frontal bone and mandibular body of the left side, causing facial deformity in the patient. Computed tomography showed an extensive hyperdense area in the frontal bone, left supraorbital margin, basilar submembrane of the left lobe jaw and submental region, with the diagnosis of osteoma, Gardner's Syndrome. Due to the extension of the frontal bone lesion and supraorbital margin, a bone plasticity was chosen through coronary access and the multiple examinations were found at the histopathological examination, which confirmed the diagnosis of osteoma. In a second surgical moment, a mandibular osteoplasty was conducted, through extended submandibular access. The postoperative follow-up of 18 months shows the area of operation, absence of pain complaints, when there are signs of recurrence of operations in the frontal bone region and in the mandible.